Innovation Pathways to Sustainability: Conversations Towards Complex Systems of Governance - Michael Lester; Marie dela Rama (Routledge, 2025)
The book offers insights into reconciling innovation with sustainability and identifying key stakeholders responsible for the reconciliation. Through conversations with experts in various fields, the intersection of innovation, sustainability, governance and complex systems in a rapidly changing climate-driven world is discussed. Countries around the world face the urgent existential challenge to tackle climate change and CO2 emissions. In its discussions of case studies of key economic sectors in Australia, this book focuses on the emerging experience with harnessing innovation to sustainability. The interdisciplinary approach to the complexity of climate change and policy making provides readers an opportunity for thoughtful discussions and lessons to be learnt from multiple angles. This is a vital resource for scholars in climate studies, innovation and sustainability that also confronts important challenges facing policymakers, government and society.
Keywords: 330; sustainable innovation; sustainable transformation; innovation policy; climate change